Victor Horta - Delevoy, Robert L. (Brussel : Elsevier, 1958)
Bibliotheek Camille Huysmans
Uitgegeven voor het Ministerie van Openbaar Onderwijs
Nederlands
Monografie
Keywords: Horta, Victor; architectuur